Políticas públicas, agricultura familiar e desenvolvimento territorial: Uma análise dos impactos socioeconômicos do PRONAF no território Médio Jequitinhonha - MG - Sandro Pereira Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– This study aimed to investigate the action of PRONAF on a territorial scope and verify the existence of social and economic impacts of this policy in the economies of cities in the Médio Jequitinhonha territory. This study searched to assess the territorial incidence of public policy in this case PRONAF in terms of their impacts on economies strongly characterized by rural activities and a large contingent of family farmers. Through instrumental Statistical Data Panel, we analyzed the impact of PRONAF in key economic variables of cities of the territory. The results indicate that PRONAF has contributed to the development of local economies, especially those cities with high demand for these credits, which serve as a source of liquidity for the handling of its economic activities.
Keywords: R11; H75; 330